Exploring the Impact of Heterogeneous Environmental Regulations on Green Innovation Efficiency: Evidence from China’s Yangtze River Economic Belt - Xiong, Ruochan; Gao, Da (Systems (Basel), 2023)
Enhancing environmental regulation (ER) is an effective way to improve the green innovation efficiency (GIE) of the Yangtze River Economic Belt (YREB) and the key to achieving the target of carbon peaking and neutrality. Using the data of 103 cities in YREB in 2013–2019, this paper explores the effect of heterogeneous ER on GIE. The results of the study are as follows: first, we categorize environmental regulations into formal and informal environmental regulations and explore their impact on green innovation efficiency separately. The results show that both formal and informal environmental regulations can effectively promote GIE in the YREB urban agglomeration. Second, the Spatial Durbin Model (SDM) model is used to analyze the spatial effect. The results show that there are spatial effects between heterogeneous environmental regulations and GIE, and environmental regulation can significantly strengthen GIE through positive spatial effects. Third, this paper uses the threshold model to explore the non-linear relationship between environmental regulation and green innovation efficiency. The results show that as ER increases, the positive effect on GIE increases, and this interesting finding holds for both formal and informal environmental regulations. Fourth, the mediating effect model is used to examine whether green technological innovation and industrial structure upgrading exert mediation effects on how environmental regulations affect GIE. The research results can provide effective policy recommendations to promote the green development of the cities in YREB.